A Mapping Global Value Chain HYBE Co, Ltd: Case Study Album "17 is Right Here" Seventeen - Dewi, Ayunda Roliana; Purbantina, Adiasri Putri (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
In today's globalized era, the world's economic system is increasingly interconnected through a global production network known as the Global Value Chain (GVC). This involves production stages located in different countries as companies expand globally to access new markets. While the GVC concept was first used in the manufacturing sector, it can now be applied to the creative industry. This study uses De Voldere's (2017) concept of the Global Music Value Chain to examine the production chain of HYBE Co., Ltd.'s album "17 Is Right Here" by Seventeen. Using a qualitative case study methodology, the research uncovers a transnational network of contributors involved in the album's production, from creation to distribution, exhibition, and reaching consumers. This transnational network adds value to HYBE Co., Ltd.'s music products, allowing them to compete in the global music market. Furthermore, technological advancements have supported the international reach of HYBE Co., Ltd.'s music products.